L'uvre de Lucien Tesnière lectures contemporaines - Neveu, Franck; Roig, Audrey (De Gruyter, 2022)
Efficient, simple, and empirically grounded, Lucien Tesnière's principles of structural syntax have remained to this day very popular among linguists. Far beyond the field of syntax itself, the Elements of Structural Syntax have found lasting echo in all branches of linguistics. This volume offers a contemporary appraisal of Tesnière's legacy